2014
DOI: 10.1088/1674-1056/23/1/014205
|View full text |Cite
|
Sign up to set email alerts
|

Controllable beating signal using stored light pulse

Abstract: Controllable beating signal using stored light pulse * Wang Lei(王 磊) a) , Yang Qing-Yu(杨庆禹) a)b) , Wang Xiao-Xiao(王潇潇) a) , Luo Meng-Xi(罗梦希) a) , Fan Yun-Fei(范云飞) a) , Kang Zhi-Hui(康智慧) a) , Dai Tian-Yuan(戴天缘) a) , Bi Sheng(毕 升) a) , Wang Hai-Hua(王海华) a)c) † , Wu Jin-Hui(吴金辉) a) ‡ , and Gao Jin-Yue(高锦岳) a) a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Zinc slag therefore provides an important source of indium. [7][8][9] Several processes have been proposed for recovering indium from zinc slag. Dai et al 10 reported a process for extracting indium that involved neutral leaching, concentrated sulfuric acid curing leaching, and alkali leaching; a 99.7% indium leaching ratio was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc slag therefore provides an important source of indium. [7][8][9] Several processes have been proposed for recovering indium from zinc slag. Dai et al 10 reported a process for extracting indium that involved neutral leaching, concentrated sulfuric acid curing leaching, and alkali leaching; a 99.7% indium leaching ratio was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Pr 3+ : Y 2 SiO 5 (Pr:YSO) crystal is chosen as the experimental medium due to its spectrum properties of narrow spectrum line and long decoherence time. [22][23][24] Under the EIT condition, the optical image carried by the probe pulse is slowed in the crystal. By manipulating the spectrum of applied control fields, the slowed image is transferred into two different information channels.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Some physical phenomena related to EIT effect have been performed experimentally by using doped solids. [17][18][19][20][21][22] In the present work, we experimentally investigate the multiple frequency conversion via atomic spin coherence by EIT-based light storage in a Pr 3+ :Y 2 SiO 5 (Pr:YSO) crystal. The essence of this multiple frequency conversion is fourwave mixing based on stored atomic spin coherence.…”
Section: Introductionmentioning
confidence: 99%